EVALUASI SIKAP KERJA SEBAGAI RISIKO NYERI PUNGGUNG BAWAH - I Gede Purnawinadi; Andrew Rumegang (Jurnal Skolastik Keperawatan, 2019)
ABSTRACT Introduction: Low back pain (NPB) is the second leading cause of global disability in musculoskeletal problems, with the highest prevalence in Indonesia being among farmers. A non-ergonomic work attitude is at risk for lower back pain. Purpose: This study identified work attitudes as a risk in relation to the incidence of low back pain. Method: This study was an observational analytic cross-sectional approach conducted on 32 farmers in Karowa Village using Rapid Entire Body Assessment (REBA) to evaluate work attitudes and questionnaires to measure complaints of lower back pain. Results: The working attitude of farmers was 77.4% at high risk and 93.7% of farmers complained of moderate pain. There is a significant relationship between work attitude and lower back pain in farmers with a positive and strong direction. Discussion: The more it is not ergonomic the working attitude of farmers is, the more at risk of developing complaints of lower back pain. Community and farmers are expected to do work safely such as avoiding overloading of shoulders, often changing positions or stretching the body while working, and if possible do work alternately. Keywords: Evaluation, Work Attitude, Risk, Pain, Lower Back.